TEMPO-Oxidized Bacterial Cellulose Pellicle with Silver Nanoparticles for Wound Dressing - Wu, Chun-Nan; Fuh, Shih-Chang; Lin, Shin-Ping; Lin, Yen-Yi; Chen, Hung-Yueh; Liu, Jui-Ming; Cheng, Kuan-Chen (Biomacromolecules, 2018)
Biocompatible bacterial cellulose pellicle (BCP) is a candidate for biomedical material such as wound dressing. However, due to lack of antibacterial activity, to grant BCP with the property is crucial for its biomedical application. In the present study, BCP was modified by 2,2,6,6-tetramethylpiperidine-1-oxyl radical (TEMPO)-mediated oxidation using TEMPO/NaClO/NaBr system at pH 10 to form TEMPO-oxidized BCP (TOBCP) with anionic C6 carboxylate groups. The TOBCP was subsequently ion-exchanged in AgNO3 solution and silver nanoparticles (AgNP) with diameter of ∼16.5 nm were in situ synthesized on TOBC nanofiber surfaces by thermal reduction without using a reducing agent. Field emission scanning electron microscopy, X-ray diffraction, X-ray photoelectron spectra, Fourier transform infrared spectroscopy, and thermogravimetric analysis were carried out to confirm morphology and structure of the pellicles with AgNP. The AgNP continuously released Ag+ with a rate of 12.2%/day at 37 °C in 3 days. The TOBCP/AgNP exhibited high biocompatibility according to the result of in vitro cytotoxicity test (cell viability >95% after 48 h of incubation) and showed significant antibacterial activities of 100% and 99.2% against E. coli and S. aureus, respectively. Hence, the highly biocompatible and highly antibacterial TOBCP/AgNP prepared in the present study is a promising candidate for wound dressing.